ANALISIS DAMPAK EL NINO TAHUN 2015 TERHADAP PENDAPATAN PETANI PISANG DI KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Ahmad Syafe’i; Zainal Abidin; Achdiansyah Soelaiman (Lampung University, 2018)
This study aims to determine the impact of El Nino on income of banana farmers and identifying mitigation of banana farmers to reduce the impact of El Nino. The research is conducted in Ketapang Sub District, Southern Lampung. The respondents are 49 banana farmers. The first objective was analyzed by income, and t-test indicators. The second objective is analyzed descriptively by mitigation undertook by farmers. The results showed that El Nino had significant impact on income of banana farmer in Ketapang Sub District of South Lampung in which income of banana farmers decreased by 37.85 percent. The mitigation done by banana farmers during El Nino were to reduce the banana seedlings, cut the banana leaves and not to use pesticides. Key words: Banana farming, El Nino, impact, welfare analysis